Rapid sea level rise and ice sheet response to 8,200-year climate event - Cronin, T. M.; Vogt, P. R.; Willard, D. A.; Thunell, R.; Halka, J.; Berke, M.; Pohlman, J. (Geophysical Research Letters, 2007)
The largest abrupt climatic reversal of the Holocene interglacial, the cooling event 8.6 - 8.2 thousand years ago (ka), was probably caused by catastrophic release of glacial Lake Agassiz-Ojibway, which slowed Atlantic meridional overturning circulation (AMOC) and cooled global climate. Geophysical surveys and sediment cores from Chesapeake Bay reveal the pattern of sea level rise during this event. Sea level rose similar to 14 m between 9.5 to 7.5 ka, a pattern consistent with coral records and the ICE- 5G glacio-isostatic adjustment model. There were two distinct periods at similar to 8.9 - 8.8 and similar to 8.2 - 7.6 ka when Chesapeake marshes were drown as sea level rose rapidly at least similar to 12 mm yr(-1). The latter event occurred after the 8.6 - 8.2 ka cooling event, coincided with extreme warming and vigorous AMOC centered on 7.9 ka, and may have been due to Antarctic Ice Sheet decay.
id: 810; 225MA Times Cited:4 Cited References Count:32Y